Prader-Willi Syndrome: Kyphoscoliosis is an underdiagnosed problem in young patients - Tahboub S; Gross-Tsur V; Hirsch JH; Arzi H (International Journal of Spine Research - Peertechz Publications, 2021)
Prader-Willi Syndrome (PWS) is a complex, neurogenetic, multisystem disorder with a prevalence of 1:15000 to 1:30000, caused by lack of expression of genes in the paternally inherited chromosome 15q 11.2-q13. In this report we aim to characterize and increase awareness of kyphoscoliosis in these children. Routine orthopedic examination for young children with PWS is essential in order to avoid medical complications and minimize the need for surgery.